Relocating the law of geographical indications - Gangjee, Dev (Cambridge: Cambridge University Press, 2012)
'There is huge variation in the nature, scope and institutional forms of legal protection for valuable geographical brands such as Champagne, Colombian coffee and Darjeeling tea. Although regional products are becoming more significant to producers, consumers and policy makers, the international legal regime under the TRIPs Agreement remains unclear. Adopting a historical approach, Dev Gangjee explores the rules regulating these brands within international intellectual property law. He traces the emergence of geographical indications as a distinct category and investigates the link between regional products and their places of origin. The research addresses longstanding puzzles, such as the multiplicity of regimes operating in this area; the recognition of the link between product and place and its current articulation in the TRIPs definition; the varying scope of protection; and the extent to which geographical indications ought to be treated as a category distinct from trade marks'--
Machine generated contents note: 1. Introduction: locating geographical indications; Part I: 2. The indication of source: Paris and Madrid; 3. The appellation of origin in France; 4. The appellation of origin in the Lisbon Agreement; Part II: 5. TRIPs today; 6. TRIPs tomorrow?; 7. Conclusions: re-locating geographical indications.
Includes bibliographical references and index.
Keywords: Agreement on Trade-Related Aspects of Intellectual Property Rights -- (1994); Marks of origin; Intellectual property (International law)